Influence of culture conditions on the secretome of mesenchymal stem cells derived from feline adipose tissue: Proteomics approach - Lara, Maria Laura [UNESP]; Carvalho, Marcos Gomides [UNESP]; de Souza, Fabiana Ferreira [UNESP]; Schmith, Rubia Alves [UNESP]; Codognoto, Viviane Maria [UNESP]; De Vita, Bruna [UNESP]; Freitas Dell'Aqua, Camila de Paula [UNESP]; Landim, Fernada da Cruz [UNESP]; Alvarenga, Marina Landim e [UNESP] (Elsevier, 2023)
This study aimed to describe the secretome of mesenchymal stem cells derived from feline adipose tissue (AD-MSCs) and compare the effects of different culture conditions on AD-MSC proteomics using a shotgun approach. Adipose tissue was collected from 5 female cats and prepared to culture. Conditioned media was collected at third passage, in which the cells were cultured under 4 conditions, normoxia with fetal bovine serum (N + FBS), hypoxia with FBS (H + FBS), normoxia without FBS (N – FBS), and hypoxia without FBS (H – FBS). Then, the secretome was concentrated and prepared for proteomic approaches. Secretomes cultured with FBS-free medium had more than twice identified proteins in comparison with the secretomes cultured with FBS. In contrast, hypoxic conditions did not increase protein amount and affected only a small proteome fraction. Relevant proteins were related to the extracellular matrix promoting environmental modulation, influencing cell signaling pathways, and providing a suitable environment for cell proliferation and maintenance. Moreover, other proteins were also related to cell adhesion, migration and morphogenesis. Culture conditions can influence protein abundance in AD-MSC secretome, and can give also more specificity to cell and cell-free treatments for different diseases.
Keywords: Conditioned medium; Felis catus; Hypoxia-culture; Proteomics; Serum-free-culture; Stem cell